2002
DOI: 10.1002/polb.10354
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between melting behavior and ringed spherulites in poly(trimethylene terephthalate)

Abstract: The lamellar types as revealed by the multiple melting peaks and possible mechanisms of ringed spherulites in poly(trimethylene terephthalate) (PTT) were analyzed with differential scanning calorimetry (DSC), optical microscopy, and scanning electron microscopy. Several interesting correlations were found. If PTT is melt-crystallized in a certain temperature range, it shows multiple melting peaks and rings in PTT. Once rings are formed in the original melt-crystallized PTT, they do not disappear but persist an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 34 publications
1
62
0
Order By: Relevance
“…For example, Ho, et al [3], Wu, et al [4], Hong et al [12], and Chuang, et al [13] shared similar results in that the banded structure could only be obtained at Tc = 195-215 °C. Xue, et al [43] reported banded spherulites formation at Tc = 170-195 °C.…”
Section: Figure 1 Crystallization Kinetics and The Related Morphologmentioning
confidence: 75%
See 3 more Smart Citations
“…For example, Ho, et al [3], Wu, et al [4], Hong et al [12], and Chuang, et al [13] shared similar results in that the banded structure could only be obtained at Tc = 195-215 °C. Xue, et al [43] reported banded spherulites formation at Tc = 170-195 °C.…”
Section: Figure 1 Crystallization Kinetics and The Related Morphologmentioning
confidence: 75%
“…For example, Ho, et al [3], Wu, et al [4], Hong et al [12], and Chuang, et al [13] shared similar results in that the banded structure could only be obtained at T c = 195-215 • C. Xue, et al [43] reported banded spherulites formation at T c = 170-195 • C. Wang, et al [3] found the lower and upper limitations of T c for banded spherulite formation are 135 • C and 165 • C, respectively. Rosenthal, et al [9] reported that the achiral PTT lamellae inverted their chirality at a certain crystallization temperature, separating the banded spherulites at lower temperature region from those at higher temperature region.…”
Section: The Effect Of Sample Thicknessmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphology and thermal behavior of a crystalline PTT are usually very complicated and only one crystal modification with a triclinic unit cell has been identified so far [4,5]. It has been reported that the multiple melting behaviors of PTT vary with their preparation conditions revealed by differential scanning calorimetry (DSC) [6][7][8][9]. The multiple melting peaks are mainly explained by (i) the melting of crystalline entities with different stability and/or (ii) the meltingrecrystallization-remelting of the imperfect crystals.…”
mentioning
confidence: 99%